Is antegrade K-wire pinning better than retrograde pinning for distal radius fracture? A comparative study - Keshava, Nischay Kenjige; Gedam, Prashant N.; Mhaisane, Sahil; Naik, Ketan; Dakhode, Shubham (International Journal of Research in Orthopaedics, 2022)
Background: The treatment of distal end radius has undergone tremendous changes over the years due to better understanding of the fracture anatomy, mechanism of injury and development of newer techniques and implants. The objective of treatment of distal end radius fracture is to restore the anatomy and to obtain early function. Percutaneous pinning is a minimally invasive technique to maintain the reduction and prevent re-displacement of the fracture fragments. Sato et al. introduced a technique of fixation for the unstable extra-articular distal radial fractures by manual reduction and antegrade intra-medullary pinning. Methods: A retrospective study with a sample size of 30, where 15 of the selected patients had undergone antegrade fixation and the rest 15 had undergone retrograde fixation. Results: Patients were evaluated for functional and radiological outcomes after a mean follow up of one year. No statistically significant difference was found between the two methods. Conclusions: Both the procedures were effective in managing the distal radius fracture with preservation of fracture hematoma. However soft tissue complications were less in antegrade pinning as compared to retrograde.